Expression of genes related to damage repairs on simple ribbon (ERCC8, ERCC6, ERCC5, XPA and XPC) in DNA em patients with myelodisplasica syndrome - Allan Rodrigo Soares Maia (2016)
Myelodysplastic Syndrome (MDS) is a group of clonal diseases of hematopoietic progenitor cells, characterized by peripheral cytopenia (s), dysplasia of one or more myeloid cell lines and increased risk of developing acute myeloid leukemia. SMD is considered a disease of the elderly, as approximately 80% of patients over 60 years are diagnosed with the disease. The causes of MDS are known in only 15% of cases. Regarding environmental factors as triggers of MDS, the use of prior chemotherapy, especially of alkylating agents and purine analogs and radiotherapy may be included. The pathogenesis of SMD involves DNA damage in hematopoietic stem cells, also resulting from single stranded DNA damage (SSB) in the DNA having three mechanisms: base excision repair (BER), base pair mismatch repair (MMR), and repair By nucleotide excision (NER), as repair processes necessary to ensure the genomic stability of stem cells. This cohort study aimed to evaluate the mRNA expression level of the single-stranded DNA repair mechanism, ERCC8 (CSA), ERCC6 (CSB) acting on the transcription-linked nucleotide excision repair mechanism (TC (XPG) and XPA acting at the confluence of the GG-NER and TC-NER subunits, associating the molecular findings with clinical variables (NER), XPC acting on the nucleotide excision repair mechanism linked to the global genome (GG-NER), ERCC5 And socio- demographic characteristics of patients with Myelodysplastic Syndrome. This analysis was based on the qPCR methodology, between bone marrow samples from 74 patients with MDS and 10 bone marrow samples from healthy elderly volunteers. Patients with MDS were diagnosed according to the criteria proposed by the World Health Organization and stratified according to the prognostic criteria established by the revised International Prognostic Score Index. With this study, it was possible to identify that: 1. patients diagnosed with hypocellular MDS presented increased levels of XPA and XPC gene expression and reduced ERCC8 (CSA) gene expression level; 2. Increased levels of ERCC8 (CSA), ERCC5 (XPG) and XPA gene were identified in poorer prognostic variables for MDS; 3. increased expression of the ERCC6 (CSB), ERCC5 (XPG) and XPA genes in cytopenic profiles representative of a more aggressive disease picture was observed; 4. MDS patients with increased ERCC8 (CSA) gene expression levels exhibited longer survival, and when increased expression levels of the ERCC5 (XPG), XPA and XPC genes exhibited lower survival; 5. In the analysis of correlations, the expression of the XPA gene showed a correlation of 26.8% with the expression of the ERCC5 gene (XPG), as well as, the expression of the XPA gene showed a 70.5% correlation with the expression of the XPC gene and, finally, XPC gene expression was found to have a 36.7% correlation with ERCC5 (XPG) gene expression.